KARAKTERISTIK FISIK KIMIA DAN ORGANOLEPTIK DODOL KERING SARI BUAH SRIKAYA DARI BERBAGAI KONSENTRASI CARBOXYMETHYLCELLULOSA - Pratiwi Karman, Syahraeni Kadir, Gatot Siswo Hutomo, Ririn (AGROTEKBIS, 2016)
This study aims to determine the effect of various concentration of CMC of physical characteristics, chemical and organoleptic of dodol dried fruit made from sugar apple and to obtain an optimal CMC concetration on physical characteristics, chemical and organoleptic of the product by preference of panelists. This research was conducted at the Laboratory of Agricultural Technology, Faculty of Agriculture, Tadulako University, Palu on February to April 2015. This study used a CRD (completely randomized design) for quality analysis of physical and chemical treatment which consists of 4 levels, namely the concentration of CMC 1% 2% 3% and 4%. As for the test organoleptic properties using a Randomized Block Design (RBD). The result showed that the consentration of CMC did not affect the oil holding capasity, water content, and total fiber, while the solubility analysis, the water holding capasity and vitamin C showed that the concentration of CMC significantly affect the texture, color, and flavor. Based on the analisys concluded that the higher the connsentration of CMC, the higher the quality of the product particularly the preference level of the flavor and color.